Dialogue in teacher qualitative inquiry: does it affect teacher-researchers and their learners or not? - Wiśniewska, Danuta (Glottodidactica, 2011)
The aim of this study was to explore: 1) whether the student-teachers (as researchers) enter into a dialogue with their learners (the researched) in the course of their research; 2) what is the nature of this dialogue; 3) what role this dialogue plays in the teachers’ and the learners’ lives. In this study I draw on teachers’ narratives which were stimulated by questions which emerged after having read the research chapters of MA theses written in the field of EFL learning and teaching.